Experimental Transmission of Karshi (Mammalian Tick-Borne Flavivirus Group) Virus by Ornithodoros Ticks >2,900 Days after Initial Virus Exposure Supports the Role of Soft Ticks as a Long-Term Maintenance Mechanism for Certain Flaviviruses. - Michael J Turell (Public Library of Science (PLoS), 2015)
Members of the mammalian tick-borne flavivirus group, including tick-borne encephalitis virus, are responsible for at least 10,000 clinical cases of tick-borne encephalitis each year. To attempt to explain the long-term maintenance of members of this group, we followed Ornithodoros parkeri, O. sonrai, and O. tartakovskyi for >2,900 days after they had been exposed to Karshi virus, a member of the mammalian tick-borne flavivirus group.Ticks were exposed to Karshi virus either by allowing them to feed on viremic suckling mice or by intracoelomic inoculation. The ticks were then allowed to feed individually on suckling mice after various periods of extrinsic incubation to determine their ability to transmit virus by bite and to determine how long the ticks would remain infectious. The ticks remained efficient vectors of Karshi virus, even when tested >2,900 d after their initial exposure to virus, including those ticks exposed to Karshi virus either orally or by inoculation.Ornithodoros spp. ticks were able to transmit Karshi virus for >2,900 days (nearly 8 years) after a single exposure to a viremic mouse. Therefore, these ticks may serve as a long-term maintenance mechanism for Karshi virus and potentially other members of the mammalian tick-borne flavivirus group.